Comparison of Outcomes in Patients with Obesity Between Two Administration Routes of Omeprazole After Laparoscopic Sleeve Gastrectomy: An Open-Label Randomized Clinical Trial - Tan Q; Gao Y; Zhang P; Huo Y; Lu Y; Huang W (Dove Medical Press, 2021)
Qin Tan,1,* Yanding Gao,1,* Pin Zhang,2 Yan Huo,3 Yihan Lu,4,5 Weifeng Huang1 1Department of Critical Care, The Sixth People’s Hospital, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Department of General Surgery, The Sixth People’s Hospital, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 3Department of Pharmacy, The Sixth People’s Hospital, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 4Department of Epidemiology, School of Public Health, Fudan University, Shanghai, People’s Republic of China; 5National Health Commission Key Laboratory of Health Technology Assessment, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weifeng HuangDepartment of Critical Care, The Sixth People’s Hospital, Shanghai Jiao Tong University, No. 600 Yi Shan Road, Shanghai, 200233, People’s Republic of ChinaEmail breeze-huang@hotmail.comBackground: The effect of different administration routes of omeprazole remains unclear on the recovery in patients with obesity after laparoscopic sleeve gastrectomy (LSG).Methods: We designed a randomized clinical trial enrolling 120 patients with a BMI≥ 32.5 kg/m2 after LSG. They were randomized into two groups to be administered with omeprazole by rapid intravenous injection (group A) or by continuous micropump infusion (group B). The plasma concentration of omeprazole was monitored upon initiating administration. Change in intragastric pH and gastrointestinal symptoms during follow-up served as indicators for therapeutic evaluation.Results: Patients in the two groups showed no difference in the AUC curves (P=0.25), but group A had significantly higher peak concentration (P< 0.001), and shorter time to reach peak concentration after administration (P< 0.001), compared to group B. Before and after the administration of omeprazole, the average change in intragastric pH was much lower in group A (0.031 ± 0.61) than in group B (0.48 ± 0.74) (P=0.004). The incidence of gastrointestinal symptoms was similar between the two groups (P=0.85); however, the average duration of remaining symptoms was longer in group A (3.97 months; 95% CI, 2.90– 5.04) than in group B (2.82 months; 95% CI, 2.01– 3.63) (P=0.04).Conclusion: Continuous micropump infusion of omeprazole may improve the outcomes in patients with obesity after LSG.Trial registration: China Clinical Trial Registration Center (ChiCTR), ChiCTR-IPR-17013365. Registered 13 November 2017. http://www.chictr.org.cn/showproj.aspx?proj=22892.Keywords: obesity, laparoscopic sleeve gastrectomy, omeprazole, gastrointestinal symptoms